The Spiral Curriculum: implications for online learning - Masters, Kenneth (BioMed Central, 2007)
BACKGROUND: There is an apparent disjuncture between the requirements of the medical spiral curriculum and the practice of replacing previous online material in undergraduate courses. This paper investigates the extent to which students revisit previous online material for the purposes of building the educational spiral, and the implications for the implementation of a Faculty's Learning Management System implementation. METHODS: At the University of Cape Town, medical students' last date of access to 16 previous online courses was determined. Students completed a survey to determine their reasons for revisiting this material and the perceived benefits of this availability. RESULTS: 70% of the students revisited their previous online courses. The major reasons were to review lecture presentations, lectures notes, and quizzes. The perceived benefits were for understanding new material, preparation for assessments, and convenience. Although student comments were not always in line with the concept of the spiral curriculum, most referred to processes of building on previous work, and some mentioned the spiral curriculum specifically. CONCLUSION: This study suggests that the practice of replacing previous online courses may hinder rather than support student learning. Although students visit previous material for ranges of reasons, a large number are aware of the spiral curriculum, and use the online environment to build upon previous material. Any practice, which entails replacing material and redesigning curricula content may be detrimental to the students' future learning needs, and such activities may need revision.